1988
DOI: 10.1063/1.99447
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous co-diffusion effects of germanium on group III and V dopants in silicon

Abstract: Anomalous diffusion effects are observed when germanium is co-diffused with phosphorus, boron, or arsenic in inert or oxidizing ambients. The germanium, an uncharged column IV dopant with a covalent radius close to that of silicon, appears to alter the point defect population in the silicon lattice. During oxidation, the usual oxidation enhanced diffusion is not observed when Ge is present in the lattice. The anomalous tail diffusion of high-concentration phosphorus is also reduced when Ge is present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
0
1

Year Published

1988
1988
1996
1996

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 9 publications
6
19
0
1
Order By: Relevance
“…The elastic interaction caused by the difference in atomic size between Ge and Si is relatively weak and has local nature, whereas the effect of OED retardation is observed experimentally outside the Ge-containing layer [4,5], i.e., it is of long-range nature. In thermal oxidation of silicon, Ge is rejected by the growing SiO 2 and is accumulated in the surface layer [6,7].…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…The elastic interaction caused by the difference in atomic size between Ge and Si is relatively weak and has local nature, whereas the effect of OED retardation is observed experimentally outside the Ge-containing layer [4,5], i.e., it is of long-range nature. In thermal oxidation of silicon, Ge is rejected by the growing SiO 2 and is accumulated in the surface layer [6,7].…”
Section: Introductionmentioning
confidence: 95%
“…According to modern concepts [1][2][3], the oxidation-enhanced diffusion (OED) and an increase in the size of extrinsic stacking faults result from generation of self-interstitials (SI) at the moving SiO 2 /Si interface. Secondary-ion mass spectrometry (SIMS) [4,5] and the spreading resistance technique [4] demonstrated that introduction of Ge impurity by implantation [4] or by deposition of a thin SiGe layer on the Si surface [5] depresses the OED of B and P dopants. An analysis of experimental B concentration distributions in terms of the mathematical model of diffusion-segregation redistribution by means of the SUPREM-III software has shown the following.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The major feature of this process is fluorine and germanium pre-implantation, which allows shallow sourcddram formation. Germanium was implanted to amorphize the polysilicon gate and the silicon substrate (3). The doping of the sourcddrain and the gate electrode was simultaneously performed using phosphorus and boron ions.…”
Section: Device Fabricationmentioning
confidence: 99%